2016
DOI: 10.1038/srep37345
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant-like activity of AC-5216, a ligand for 18KDa translocator protein (TSPO), in an animal model of diabetes mellitus

Abstract: Diabetes mellitus is a chronic disease that is associated with depression. Also, depression is common in adults with type 2 diabetes mellitus (T2DM). Translocator protein (18kDa) (TSPO) and allopregnanolone play an important role in the depression treatment. However, few studies have evaluated TSPO and allopregnanolone in the treatment of depression in T2DM. AC-5216, a ligand for TSPO, produces anxiolytic- and antidepressant-like effects in animal models. The present study aimed to explore antidepressant-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 70 publications
0
25
0
1
Order By: Relevance
“…Several studies have suggested a relationship between DM and psychiatric deficits, demonstrated by increased immobility time in the FST in STZ‐diabetic mice, and decreased time spent in an open arm in the elevated plus maze test (anxiety‐like behaviour) . More recently, another study demonstrated that rats with diabetes induced by a combination of high fat diet and STZ exhibit various depression‐like behavioural deficits, such as decreased sucrose preference and increased latency to feeding in the novelty suppression of feeding test . Details of the depression‐like phenotypes exhibited by DM models have been described elsewhere .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested a relationship between DM and psychiatric deficits, demonstrated by increased immobility time in the FST in STZ‐diabetic mice, and decreased time spent in an open arm in the elevated plus maze test (anxiety‐like behaviour) . More recently, another study demonstrated that rats with diabetes induced by a combination of high fat diet and STZ exhibit various depression‐like behavioural deficits, such as decreased sucrose preference and increased latency to feeding in the novelty suppression of feeding test . Details of the depression‐like phenotypes exhibited by DM models have been described elsewhere .…”
Section: Discussionmentioning
confidence: 99%
“…18 More recently, another study demonstrated that rats with diabetes induced by a combination of high fat diet and STZ exhibit various depression-like behavioural deficits, such as decreased sucrose preference and increased latency to feeding in the novelty suppression of feeding test. 19 Details of the depression-like phenotypes exhibited by DM models have been described elsewhere. 20 Our finding that SDT fatty rats show depression-like behavioural changes provides further support for previous studies that have used classical animal models of DM.…”
Section: Several Behavioural Tests To Assess Depression-like Phenotypesmentioning
confidence: 99%
“…The TSPO ligands are indeed exploited for anti-inflammatory and neuroprotective effects (Qiu et al, 2016;Scholz et al, 2015).…”
Section: Mitochondrial Cholesterol and Oxysterols In Neurodegenerationmentioning
confidence: 99%
“…While cholesterol synthesis inhibitors such as the "blockbuster" statins (Cholesterol TreatmentTrialists' Collaboration, 2015) occupy an elite place in cholesterol modulation, it is perhaps time to look beyond this strategy and turn to more subtle and selective mechanisms of cholesterol shuttling.The TSPO ligands are indeed exploited for anti-inflammatory and neuroprotective effects(Qiu et al, 2016;Scholz et al, 2015).In a rat model of hypercholesterolaemia, ischaemia-reperfusion injury results in mitochondrial sterol (both cholesterol and oxysterol) accumulation in mitochondria (Paradis, Leoni, Caccia, Berdeaux, & Morin, 2013), which can be ablated by TSPO ligands such as SSR180575 (a benzodiazepine), 4′-chlorodiazepam, or TRO40303. While cholesterol synthesis inhibitors such as the "blockbuster" statins (Cholesterol TreatmentTrialists' Collaboration, 2015) occupy an elite place in cholesterol modulation, it is perhaps time to look beyond this strategy and turn to more subtle and selective mechanisms of cholesterol shuttling.The TSPO ligands are indeed exploited for anti-inflammatory and neuroprotective effects(Qiu et al, 2016;Scholz et al, 2015).In a rat model of hypercholesterolaemia, ischaemia-reperfusion injury results in mitochondrial sterol (both cholesterol and oxysterol) accumulation in mitochondria (Paradis, Leoni, Caccia, Berdeaux, & Morin, 2013), which can be ablated by TSPO ligands such as SSR180575 (a benzodiazepine), 4′-chlorodiazepam, or TRO40303.…”
mentioning
confidence: 99%
“…The overexpression of TSPO in honey bee nurses and foragers may be related to the control of cellular stress that affects worker bee behaviors. 22 TSPO is suggested to be a novel therapeutic target for depression behavior, 23 and TSPO expression may constitute a biomarker of brain inflammation and reactive gliosis that could be monitored using TSPO ligands as neuroimaging agents. 12 TSPO is also a biomarker of adult separation anxiety disorder (ASAD), 21 and the decreased expression level of TSPO affects the mitophagy signaling pathway in learned helplessness mice.…”
mentioning
confidence: 99%